An East Meets West Approach to the Understanding of Emotion Dysregulation in Depression: From Perspective to Scientific Evidence - Ye, Jiajia; Cai, Shuhe; Cheung, Wai Ming; Tsang, Hector W. H. (Frontiers in Psychology, 2019)
Depression, an emotion regulation disorder, is a prevalent mental illness in the world. Meanwhile, traditional Chinese medicine (TCM) has been increasingly regarded as a promising and effective alternative therapy approach for patients with depression. Despite many years of research on depression, the current understanding of the pathological mechanism of depression based on TCM theories is still in its infancy. Due to the lack of scientific evidence in the past, TCM is not fully recognized by researchers around the world. This review firstly summarizes the pathogenesis and etiology of depression in terms of both Eastern and Western medical systems. Secondly, it adopts an integrated Eastern and Western approach to propose some plausible neurophysiological pathways linking the liver, spleen, and heart functions explicated in TCM theory. The aim of this theoretical review is to bridge the knowledge gap between Eastern and Western medicine, which may better explain the pathology of depression.